The Effects of Early Life Stress on the Brain and Behaviour: Insights From Zebrafish Models - Eachus, Helen; Choi, Min-Kyeung; Ryu, Soojin (Frontiers in Cell and Developmental Biology, 2021)
The early life period represents a window of increased vulnerability to stress, during which exposures can lead to long-lasting effects on brain structure and function. This stress-induced developmental programming may contribute to the behavioural changes observed in mental illness. In recent decades, rodent studies have significantly advanced our understanding of how early life stress (ELS) affects brain development and behaviour. These studies reveal that ELS has long-term consequences on the brain such as impairment of adult hippocampal neurogenesis altering learning and memory. Despite such advances, several key questions remain inadequately answered, including a comprehensive overview of brain regions and molecular pathways that are altered by ELS and how ELS-induced molecular changes ultimately lead to behavioural changes in adulthood. The zebrafish represents a novel ELS model, with the potential to contribute to answering some of these questions. The zebrafish offers some important advantages such as the ability to non-invasively modulate stress hormone levels in a whole animal and to visualise whole brain activity in freely behaving animals. This review discusses the current status of the zebrafish ELS studies and its potential as a new ELS model.